Personalised anti-inflammatory therapy for bronchiectasis and cystic fibrosis: selecting patients for controlled trials of neutrophil elastase inhibition. Issue 1 (25th March 2019) - Keir, Holly R.; Fong, Christopher J.; Crichton, Megan L.; Barth, Philip; Chevalier, Eric; Brady, Gill; Kennedy, Gwen; Zimmermann, Johann; Bruijnzeel, Piet L.B.; Dicker, Alison J.; Chalmers, James D.
Background: Neutrophil elastase (NE) has been linked to lung neutrophil dysfunction in bronchiectasis and cystic fibrosis (CF), making NE inhibition a potential therapeutic target. NE inhibitor trials have given mixed result perhaps because not all patients have elevated airway NE activity. Methods: We tested whether a single baseline sputum NE measurement or a combination of clinical parameters could enrich patient populations with elevated NE activity for "personalised medicine". Intra- and interindividual variations of total and active NE levels in induced sputum from patients with CF or bronchiectasis were monitored over 14 days. Patients with established CF and bronchiectasis (n=5 per group) were recruited. NE was measured using three different methods: one total and two active NE assays. Subsequently, we analysed the association between clinical parameters and NE from a large bronchiectasis cohort study (n=381). Results: All three assays showed a high degree of day-to-day variability (0–233% over 14 days). There were strong correlations found between all assays (p<0.0001). Despite high day-to-day variability, patients could be stratified into "high" or "low" groups based on moderate cut-off levels. In the bronchiectasis cohort study, factors most associated with high sputum NE levels were: Pseudomonas aeruginosa infection (β-estimate 11.5, 95% CI −6.0–29.0), sputum colour (β-estimate 10.4, 95% CI 4.3–16.6), Medical Research Council dyspnoea score (β-estimate 6.4, 95% CI 1.4–11.4) and exacerbation history (β-estimate 3.4, 95% CI 1.4–5.3). Collectively, P. aeruginosa infection, sputum colour and exacerbation frequency provided the greatest specificity for "high" NE (98.7%, 95% CI 7.0–99.6%). Conclusion: These results show that patients with bronchiectasis and CF can be effectively divided into "high" or "low" groups, based on sputum NE assays or clinical inclusion criteria. NE at baseline can enrich studies for "high" NE patients, while in bronchiectasis, inclusion of patients with Pseudomonas aeruginosa, purulent sputum and frequent exacerbations provides a high degree of certainty of including patients with high NE http://ow.ly/mPTS30nI8ec